Некоторые аспекты проблемы химиорезистентности - Думанский, Ю.В.; Кайряк, О.В.; Марунич, В.К. (Онкологія, 2015)
Data are analyzed about some molecular mechanisms of сhemoresistance of malignant tumors and the clinical aspects of such analysis are considered. In particular, authors pay attention to pointlessness of the use of preparations, containing a glutathione, as therapy of accompaniment during realization of chemotherapy, because it conduces to the decline of effect of treatment. It is marked that realization of therapy tamoxi fen during the course of chemotherapy streng thens its action, because besides a antiestrogen function, preparation is the inductor of apoptosis. Data, coming from that activity of genes of BRCA, participating in reparation of DNA, can serve as a parameter, dicta ting a choice between setting of taxanes and preparations of platinum, are considered. Chemotherapy is desirable to individualize taking into account the molecular-genetic features of tumor, or by determination of indivi dual sensitiveness, including by a method, worked out in the Donetsk Regional Antitumoral Center.